Evaluation of Tubing Diameter and Bean Size for Optimization of Well Production Rate - Arya Dwi Candra; Muhammad Firmansyah Hafidzullah; Rakha Reswara; Paradongan Siahaan; Dies Elita Budiyanti; Zainal Abidin (Jurnal POLIMESIN, 2023)
Gas field development is a costly affair, thus it is essential that each component of the production system operates properly. The objective of field optimization is to discover the parameter range that maximizes productivity. In addition, the development of natural gas reserves for both fuel and petrochemical purposes is accelerating. Well X is an approximately 4-year-old natural-flow gas well with a gas flowrate of 7.7 MMSCF/D, condensate flowrate of 55 BCPD, and water flowrate of 2 BWPD. As fluid is generated from the reservoir to the surface, the production rate of the well decreases. This well's productivity was evaluated using nodal analysis in conjunction with a comparison of tubing size and bean size. aiming to satisfy gas demand without exceeding the critical limit. The nodal analysis approach is utilized to determine the well's optimal and efficient performance. Moreover, utilizing system analysis, which is a graphical plot between the tubing size and the resulting flow rate, as depicted in Figure 6, we can determine which tubing size delivers the highest or most efficient rate at a particular moment under constant wellhead pressure (node at the wellhead). If the demand grows by 14.4 MMSCF/D, the installed tube size can be changed to 40/64" for optimization purposes. This procedure is more cost-effective because it does not squander money and does not halt gas production at the well. To satisfy the increased gas demand of 14.4 MMSCF/D, the production operator can rotate the bean or choke from its initial 24/64" size to 40/64" size.